2019
DOI: 10.1097/mph.0000000000001499
|View full text |Cite
|
Sign up to set email alerts
|

The Value of 18F-FDG PET/CT in Detecting Bone Marrow Involvement in Childhood Cancers

Abstract: Background: The aim of this study was to assess the utility of 18F-fluoro-2-deoxy-d-glucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) in assessing bone marrow involvement (BMI) compared with bone marrow biopsy (BMB) in the initial staging of pediatric patients with non-Hodgkin lymphoma (NHL), Hodgkin lymphoma (HL), Ewing sarcoma (ES), and neuroblastoma (NB). Procedure: A total of 94 patients (57 boys, 37 girls, median age 7 y, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…Four studies ( Table 3) were identified that utilized FDG-PET scans for staging of BMM in newly diagnosed ES patients. 21,29,38,39 Data from these studies were aggregated for quantitative analysis to define testing characteristics of FDG-PET scans compared to BMBA. The studies ranged in publication year from 2013 to 2019, and all were completed in a retrospective manner.…”
Section: Quantitative Analysis: Fdg-pet Scan Versus Bmbamentioning
confidence: 99%
“…Four studies ( Table 3) were identified that utilized FDG-PET scans for staging of BMM in newly diagnosed ES patients. 21,29,38,39 Data from these studies were aggregated for quantitative analysis to define testing characteristics of FDG-PET scans compared to BMBA. The studies ranged in publication year from 2013 to 2019, and all were completed in a retrospective manner.…”
Section: Quantitative Analysis: Fdg-pet Scan Versus Bmbamentioning
confidence: 99%
“…In the present study, bone marrow SUVmax and the SUVmax-ratio were two meaningful parameters for NB patients with BMI. PET/CT has high sensitivity for assessing bone marrow infiltration in pediatric malignancies [13,26]. In particular, PET has improved sensitivity in detecting BMI in patients with lymphoma and may allow patients with positive BMI confirmed by PET/CT examinations to avoid undergoing invasive BMB [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analysis suggested that 18 F-FDG PET had a higher sensitivity but lower specificity than MIBG scintigraphy in NB lesion detection [8]. Another recent meta-analysis reported a 17% pooled sensitivity of positron emission tomography (computed tomography) (PET(CT)) for the detection of bone marrow in pediatric NB in their subgroup analysis, which was significantly lower than several studies [9][10][11][12][13][14][15][16]. Superiorities of PET are high 18 F-FDG avidity of the bone marrow and imaging of the entire marrow [17].…”
Section: Introductionmentioning
confidence: 95%
“…en, 16 full-text articles were selected to read carefully, and 7 studies comprising a total of 127 patients were enrolled in the current meta-analysis finally [10][11][12][13][14][15][16]. A flow diagram of eligible literature is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation